Berpikir Visual Siswa SMA dalam Memecahkan Masalah Dimensi Tiga Berdasarkan Gaya Kognitif Field Dependent dan Field Independent - Fran Susanto; Tatag Yuli Eko Siswono; Ismail Ismail (LP. Ma'arif Janggan Magetan, 2024)
The aim of the study is to describe students’ visual thinking process in solving third dimensional problems. This research was descriptive study with qualitative approach. Two girls students with the higher rank in mathematics’ test and representing a student with field dependent cognitive style and a student with field independent cognitive style were selected as the research subject. The data were collected by giving third dimensional problems test based on Polya’s steps of problem solving and interviews. The student’s visual thinking is described based on looking, seeing, imagining, & showing process. The results shows that FI & FD student were looking & seeing in understanding the problems, seeing & imagining in devising a plan, in carying out the plan, FI student was showing relative short steps, but FD student was showing right solution in different steps. In looking back, both students was not showing a looking back process.